(untitled) (Papeles, 2009)
This article presents the results of the work done by the authors about the thought of the philosopher Plato, whose development was inside the frame of the investigation Notion and concept of representation. Especially, it focuses in Plato’s postulates about the concept of representation, that is to say, it wonders for the presence of the above mentioned concept in his vast work and for what he means with it